Le vol à main armée chez les mineurs - LeBlanc, Marc (Criminologie, 1985)
Armed robbery is rarely committed by minors, but because of the gravity of the crime, it is given considerable importance in the operations of our justice system. Since there is little data in the regard, we have investigated how such crimes, which are among the most serious, are treated by the system. We have found that these crimes are committed in an unprofessional way. From the police to the defence procedure, and going through the director of youth protection, they are dealt with fairly rapidly and in an official manner; however, the sentence is based less on the objective gravity of the crimes than on the characteristics of the minor, on his previous criminal record.